Validitas Flash Flipbook pada Submateri Pemanfaatan Keanekaragaman Hayati sebagai Tumbuhan Upacara Adat - Nur Hafizah; Syamswisna Syamswisna; Asriah Nurdini Mardiyyaningsih (Bioscientist : Jurnal Ilmiah Biologi, 2022)
Indonesia has traditional knowledge that is passed down from generation to generation. Traditional knowledge becomes a culture in rural communities or indigenous tribes of the area. One element of culture that is universal and still applies today is traditional ceremonies. Traditional ceremonies that are carried out still use plants in their activities. One of the communities that still implement it is the Dayak Kerambai tribe in Mabah Hamlet, Sanggau Regency. on Biology material, especially the sub-material of the utilization of Indonesia's biodiversity in the field of aspects and culture in accordance with syllabus 3.2. The information obtained can be implemented into flipbook flash media. Flash flipbook media is packaged simply, and attractively using four of the six stages from Borg and Gall (potentials & problems, data collection, media design and validation). This study aims to determine the appropriateness of the flash flipbook media as a learning medium for the sub-material of the use of Indonesia's biodiversity. The media were validated by 6 validators, namely 3 media experts such as 1 lecturer in Biology Education FKIP UNTAN, 1 SMA Muhammadiyah 2 teacher and 1 SMK Muhammadiyah 2 teacher and 3 material experts, 1 lecturer in Biology Education FKIP UNTAN, 1 SMA Santun teacher Untan and 1 teacher from SMA 2 Sekayam to assess the feasibility of the media and materials. The results of the flash flipbook media assessment referring to Yamasari obtained an RTVTK value of 3.81 for media experts, while RTVTK for material experts was 3.67. Flash flipbook media enriched with information on the utilization of biodiversity based on traditional ceremony plants was declared suitable to be used as a learning medium for sub-materials on the use of Indonesian biodiversity for class X SMA/MA.